Thyroid Hormone Profile in Patients Ingesting Soft Gel Capsule or Liquid Levothyroxine Formulations with Breakfast. (30th May 2016) - Cappelli, Carlo; Pirola, Ilenia; Gandossi, Elena; Cristiano, Alessandra; Daffini, Linda; Agosti, Barbara; Casella, Claudio; Castellano, Maurizio
Abstract : Background . Recently, it has been shown that liquid L-T4 formulation can be ingested with breakfast. This study looked to extend these findings by investigating whether a soft gel capsule formulation of L-T4 could also be ingested at breakfast time. Methods . 60 patients (18–65 yrs), previously submitted to thyroidectomy for proven benign goitre in stable euthyroidism receiving liquid L-T4 therapy ingested with breakfast, were enrolled. TSH, fT4, and fT3 levels were assessed in all the patients who were switched from liquid L-T4 to a soft gel capsule formulation at the same dosage of L-T4. After 6 months, TSH, fT4, and fT3 levels were determined again. Results . There were no differences in TSH levels, but fT3 and fT4 levels during treatment with the soft gel capsule were significantly lower than those at enrolment with the liquid L-T4 formulation (TSH median (min–max): 1.9 (0.5–4.0) versus 2.2 (0.5–4.5) mIU/L, fT3: 2.5 (2.4–3.1) versus 2.7 (2.4–3.3) pg/mL, p < 0.05, and fT4: 9.9 (8.0–13) versus 10.6 (8.6–13.8) pg/mL, p < 0.0001 ). Conclusion . Both liquid and soft gel formulations of L-T4 can be taken with breakfast. However, liquid L-T4 would be the preferred formulation for patients in whom even small changes in fT4 and fT3 levels are to be avoided.